The 2 minute loaded repeated jump test: Longitudinal anaerobic testing in elite Alpine ski racers - Patterson, C.; Platzer, H.-P.; Raschner, C. (Journal of Sports Science & Medicine, 2019)
This study investigated the 4-year development of anaerobic power and capacity in Austrian elite female alpine ski racers and examined the relationship between the 2-minute loaded repeated jump test (LRJT) results and ski racing performance (International Ski Federation (FIS) points). Ten Austrian elite female ski racers were tested prior to four racing seasons. The LRJT consisted of 48 loaded countermovement jumps (LCMJs) with barbell load equivalent to 20% bodyweight. Before the LRJT, maximal body mass normalized average power of a single LCMJ (PMAX) was determined. The mean jump power was calculated across all jumps in the test (P0-120). Anaerobic power (PMAX) in season 2 (32.3 ± 2.3 W·kg-1) significantly improved over season 1 (30.5 ± 2.3 W·kg-1) (p < 0.05) but there were no further differences between seasons, with season 3 at 33.5 ± 3.4 W·kg-1 and season 4 at 33.6 ± 3.0 W·kg-1. Anaerobic capacity (P0-120) increased up to season 3 by 9.2% (27.1 ± 2.8 to 29.6 ± 2.4 W·kg-1), but was significantly higher only when comparing season 4 to seasons 1 and 2 (p < 0.05). FIS points changed significantly (p < 0.05), from 18.1 ± 8.2 in season 1 to 8.4 ± 4.8 in season 4 (lower FIS points indicates better racing results). FIS points had a positive relationship with PMAX (r = -0.73, p < 0.05) and P0-120 (r = -0.64, p < 0.05) only in season 4. Improvements in FIS points from year to year did not correlate with seasonal increases in LRJT results. In conclusion, anaerobic power improved only after season 1, and anaerobic capacity changes were evident only in season 4. Ski racing performance (FIS points) correlated with LRJT test results in only season 4. The LRJT can monitor a ski racer`s anaerobic power and capacity, but does not correlate with ski racing performance.